Friend or Foe? Investigating the Alignment of English Language Teaching (ELT) Textbooks with the National English Curriculum Standards - Sukying, Apisak; Barrot, Jessie S. (The Asia-Pacific education researcher, 2025)
There is an ongoing concern regarding the alignment of textbooks with curriculum standards across different subjects. Such studies have emphasized the critical, yet complex, role of textbooks in bridging pedagogical practices with curricular reforms. The present research builds upon these discussions, by examining not only the alignment but also exploring how ELT textbooks supplement the English national curriculum. In this descriptive study, two series of high school ELT textbooks were scrutinized through both quantitative and qualitative lenses. The findings revealed notable misalignments between the learning competencies covered by the textbooks and those outlined by the national curriculum. Furthermore, the textbooks implemented a range of strategies to supplement the curriculum, actions that could be interpreted as either deficiencies or enhancements. Implications for curriculum design, textbook development, and future studies are discussed.